Blossoms Perfuming the Garden: From Peony Pavilion to Don Quixote - Xuchen, Zhu (Sinología hispánica. China Studies Review, 2016)
Based on the framework of language construction and psychoanalysis, this study analyzes love and worldly ideal, which are presented by Tang Xianzu and Cervantes in Peony Pavilion and Don Quixote. Due to the similar experience and life sentiment, the two authors showed amazing consistency on creative thinking, writing skill, creative psychology and even marriage notion, which verified the communicative idiomatum between eastern and western literature in the same era